The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1024/0301-1526/a000844
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of large diameter proximal aortic neck in endovascular aneurysm repair

Abstract: Summary. Background: Adverse morphological features of the proximal aortic neck have been identified as culprits for late failure after endovascular aneurysm repair (EVAR). Our objective was to investigate the prognostic role of wide proximal aortic neck in EVAR. Methods: We conducted a review of the literature in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to identify studies comparing outcomes of EVAR in patients with large versus small proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…These findings are consistent with previous systematic reviews that focused on individual neck characteristics. The higher odds for developing type 1a endoleak in patients with a larger neck diameter were also reported in systematic reviews by Antoniou et al 6 and Kouvelos et al 7 The current results regarding neck angulation were also consistent with findings by Qayyum et al 9 Although neck length is one of the most important neck characteristics for pre-operative planning, 4,11 this variable has not been described much in the literature. An explanation for this could be that patients with a short proximal neck length are almost exclusively treated with open surgical repair or complex (fenestrated, branched, or chimney) EVAR.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with previous systematic reviews that focused on individual neck characteristics. The higher odds for developing type 1a endoleak in patients with a larger neck diameter were also reported in systematic reviews by Antoniou et al 6 and Kouvelos et al 7 The current results regarding neck angulation were also consistent with findings by Qayyum et al 9 Although neck length is one of the most important neck characteristics for pre-operative planning, 4,11 this variable has not been described much in the literature. An explanation for this could be that patients with a short proximal neck length are almost exclusively treated with open surgical repair or complex (fenestrated, branched, or chimney) EVAR.…”
Section: Discussionsupporting
confidence: 89%
“…This finding broadly supports other studies associating large neck diameter with delayed T1aEL, increased risk of rupture, and lower overall survival rate. 20 As a result of this, the nominal endograft diameter was significantly larger in the T1aEL group as well. Nowadays, more complex EVAR procedures, like FEVAR or BEVAR, should be considered in patients who otherwise need an endograft with a nominal diameter of >30mm, to achieve sufficient seal in the infrarenal neck.…”
Section: Discussionmentioning
confidence: 77%
“…[8] Howard et al [4] reported that patients with a large proximal aortic neck had a higher rate of type 1a endoleaks and a lower five-year survival rate. In another study, Antoniou et al [17] compiled the results of nine studies that included 7,682 patients with AAAs, grouped as patients with large versus small aortic necks. The risk of death, aneurysm-related reintervention, type 1a endoleak, sac enlargement and aneurysm rupture were significantly higher in patients with a large proximal aortic neck than those with a small neck.…”
Section: Discussionmentioning
confidence: 99%